Implementasi Zikir Ratib Haddad terhadap Kecerdasan Spiritual Santri di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo: Implementation of Zikir Ratib Haddad on the Spiritual Intelligence of Santri at the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo - Syaifulloh Yazid; Khansa Hana (University of Darussalam Gontor, Indonesia, 2023)
This research examines how the implementation of Ratib Hadda's dhikr and its relationship with the spiritual intelligence of the students at the Salafiyah Syafi'iyah Islamic Boarding School, Sukorejo. The background of this research is the routine reading of Ratib Haddad in PP. Salafiyah Syafi'iyah Sukorejo which lasted quite a long time and continues until now. In fact, the recitation of this dhikr is required because it is one of the methods in the spiritual journey of the santri to gain spiritual intelligence and other benefits from this practice. In an effort to collect data and facts for this study, researchers conducted field observations to PP. Salafiyah Syafi'iyah Sukorejo and conducted direct interviews with students who had attended the readings of Ratib Haddad regularly according to the schedule of the boarding school. Ratib Haddad is a practice that contains prayers and dhikr compiled by a scholar from Hadramut, namely Habib Abdullah bin Alwi bin Muhammad al-Haddad. The recitation of this dhikr is carried out routinely after the Asar and Isha prayers regularly and in congregation. Meanwhile, regarding the reading order of Ratib Haddad's version of Salafiyah Syafi'iyah Sukorejo, the ratib readings are at the beginning, while the special ones are in the middle and then continue with prayers and subsequent readings. And the order of Ratib's readings is the result of riyadhah from KH. R.Syamsul Arifin as the founder and first caregiver at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School. With the aim of getting closer to Allah SWT, Ratib's practice has a positive influence on the souls of the students. The students feel an increase in the increase in the soul of spirituality. With the increasing spirituality of the soul, it will also increase spiritual intelligence. Therefore it is very appropriate if Ratib Haddad is in PP. Salafiyah Syafi'iyah Sukorejo is nicknamed “the soul of the Sukorejo students”.